Australia's coal seam gas boom and the LNG entry result. (12th May 2015) - Simshauser, Paul; Nelson, Tim
<x xml:space="preserve">Abstract</x> Queensland experienced extraordinary growth in booked 2P coal seam gas (CSG) reserves, rising from 3, 400 PJ in 2005 to 41, 200 PJ in 2013. Given annual domestic consumption of ca. 700 PJ/a, 2P reserves rapidly shifted from 14 to 72 years supply. Profit‐maximising firms sought to speed up commercialisation of reserves through the development of three liquefied natural gas (LNG) export plants at Gladstone. In this article, we present forecasts of Australia's east coast interconnected gas system with daily resolution using our dynamic partial equilibrium model. Modelling results show the rapid development of LNG plants combined with restrictive CSG development policies in NSW may result in unserved load from 2016. Relaxing development constraints or delaying construction of one LNG terminal by 1 year could have avoided the risk of Unserved Load events in the domestic gas market. Lessons can be learned from this CSG‐LNG boom scenario. Facilitating new gas supplies is the most efficient way of alleviating the impacts of the CSG‐LNG boom on domestic markets in the medium term. In the long‐term, Australian policymakers may consider the merits of a National Net Benefits Test to maximise welfare through appropriate coordination – as is done by policymakers in the USA – as opposed to protecting local industries through 'domestic gas reservation policies'.